Cloning and expression in Escherichia coli of the genes of the arginine deiminase system of Streptococcus sanguis NCTC 10904. - Burne, R A (1989)
The common oral bacterium Streptococcus sanguis can degrade arginine via the arginine deiminase (AD) system. The three enzymes of this system, AD, ornithine carbamyltransferase (OTC), and carbamate kinase (CK), catalyze the breakdown of arginine to ornithine, CO2, and two molecules of ammonia, with the production of ATP from ADP. The genes of the AD system, which are subject to complex regulation in the oral streptococci, have been isolated in bacteriophage lambda by screening for AD activity. The AD gene, designated arcA, was expressed from recombinant bacteriophage or in cells harboring plasmid subclones from this phage at a level up to 1,000-fold lower than the level in fully derepressed S. sanguis but apparently under the control of its own promoter. By subcloning in Escherichia coli mutants defective in anabolic OTC (argF argL) and CK (carB), it was demonstrated that the genes for S. sanguis OTC and CK were located adjacent to the AD gene. The levels of expression of the OTC and CK genes (arcB and arcC, respectively) were also very low in E. coli, although arcC expression was not as poor as arcA and arcB expression when compared with the levels found in S. sanguis. Also, arcB and arcC were unable to complement the defects in their anabolic counterparts. Introduction of the entire AD system or subclones which encoded only the AD gene into E. coli harboring defects in arginine and pyrimidine biosynthesis resulted in a 10- to 15-fold decrease in the level of AD activity, suggesting that arginine or its metabolites may regulate AD expression. Transposon mutagenesis was utilized to construct defined mutants of S. sanguis with mutations in the AD gene cluster. AD gene expression in these mutants indicated that the expression of the AD genes in this organism is strongly interrelated. The isolation and partial characterization of the arc genes represents the first step in the genetic manipulation of the AD system in the oral streptococci for analysis of the regulation of AD, analysis of the role of the system in plaque ecology, and utilization of the system to modulate the cariogenicity of dental plaque.